An exploratory study for scoping software product lines in a collaborative way - Ojeda, Marta Cecilia Camacho; Alegría, Julio Ariel Hurtado; Rodriguez, Francisco Javier Álvarez (2018 IEEE/ACM 11th International Workshop on Cooperative and Human Aspects of Software Engineering (CHASE), 2018)
Software companies are looking for strategies that allow them to be competitive and stay in the market, these companies must not be limited to create new products, they also need to improve their production and marketing processes. The Software Product Lines (SPL) is a production strategy based on planned reuse that seeks to improve productivity, decreasing the time to market and increasing quality of the products. One of the essential activities in the adoption of this approach and development of a SPL is scoping. The SPL scoping is an interdisciplinary activity that includes different visions such as business, marketing, technical aspects and context issues; therefore, the participation of different people with dissimilar and partial knowledge is a key factor in the SPL Scoping. The diversity of participants is relevant but it is not easy that people with different knowledge and interests interact with each other and agree on the scope of the product line. This paper presents an empirical analysis about the addition of collaborative practices in SPL scoping process. We contrasted the results obtained in SPL scoping when collaborative elements are used in the process, observing the execution and results obtained by two groups that followed two different methods for SPL scoping; a group used the original method and the other group followed the same process but including collaborative elements.